Hotel Building Planning in the Harau Valley Natural Tourism Area - Rahmat Hidayat; Astuti Masdar; Ronny Junnaidy (LEADER: Civil Engineering and Architecture Journal, 2026)
The planning for the Hotel Building in the Harau Valley Natural Tourism Area consists of 5 floors. The function of this building planning is to support the implementation of the planned structural element consisting of floor plates, beams, columns and foundation. Guidelines for planning reinforced concrete buildings. SNI 1726- 2019 for planning earthquake loads and SNI 1727-2020 for planning loads on buildings. In this plan, concrete quality Fc’ = 25 Mpa is used, threaded reinforcement uses steel quality 420 Mpa and plain reinforcement with steel quality 280 Mpa. From the results of the calculations that have been carried out, it can be seen that the thickness of the floor plate is 120 mm and for the roof plate it is 100 mm thick, while the beam is 30/60 cm with D22 main reinforcemen, the beam with dimensions 35/70 cm uses D22 main reinforcemen and the dimensions of the joist area 20/35 uses D16 main reinforcemen and uses Ø10 for stirrup reinforcemen. For foundation planning, use a boredpile foundation. Analyze the structure in this planning using the SAP 200 v.14 aplication.